2005
DOI: 10.1111/j.1529-8817.2005.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

NOMENCLATURAL NOTE ON A THECADINIUM SPECIES (DINOPHYCEAE, GONYAULACALES), WHICH WAS DESCRIBED AS NEW INDEPENDENTLY THREE TIMES WITHIN TWO MONTHS1

Abstract: Three Thecadinium species, independently described as new in three separate publications, are actually regarded as conspecific. The combined plate formula is Po 3 0 1a 6 00 5-7/8c 5s 6 00 0 2 0000 . The size range of the species is 38-65 lm in length and 23-42 lm in depth. It has one or two strongly lobed chloroplasts. The correct name of the species is Thecadinium yashimaense Yoshimatsu, Toriumi et Dodge 2004. Thecadinium mucosum Hoppenrath et Taylor 2004 and Thecadinium foveolatum Bolch 2004 are taxonomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In Plagiodinium belizeanum, the epitheca is atypical, very small and slightly inclined to the ventral side (Faust & Balech, 1993), differing from M. loirii. The left-handed displacement of the cingulum in M. loirii is peculiar and reminiscent of that of Thecadinium yashimaense (Bolch & Campbell, 2004;Hoppenrath et al, 2004Hoppenrath et al, , 2005Yoshimatsu et al, 2004), and also of the planktonic taxa Thecadiniopsis tasmanica and Pseudothecadinium campbellii (Croome et al, 1987;Hoppenrath & Selina, 2006). This is the reverse situation to the benthic genus Cabra where the epitheca is higher on the left side than on the right lateral side.…”
Section: Discussionmentioning
confidence: 62%
“…In Plagiodinium belizeanum, the epitheca is atypical, very small and slightly inclined to the ventral side (Faust & Balech, 1993), differing from M. loirii. The left-handed displacement of the cingulum in M. loirii is peculiar and reminiscent of that of Thecadinium yashimaense (Bolch & Campbell, 2004;Hoppenrath et al, 2004Hoppenrath et al, , 2005Yoshimatsu et al, 2004), and also of the planktonic taxa Thecadiniopsis tasmanica and Pseudothecadinium campbellii (Croome et al, 1987;Hoppenrath & Selina, 2006). This is the reverse situation to the benthic genus Cabra where the epitheca is higher on the left side than on the right lateral side.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, other taxonomically related species were found to be quite distinct. The two Thecadinium species analysed here did not cluster together: Thecadinium yashimaense (as T. inclinatum ) (HM236199) collected from Canada (held in CCCM) was later identified as T. mucosum [63] and was subsequently re-classified as conspecific to T. yashimaense and T. fovealatum [64] . However, our data showed that T. yashimaense (inclinatum) (HM236199) and T. yashimaense (HM236200) from Germany were distinct species.…”
Section: Resultsmentioning
confidence: 88%
“…It may be thought of as one of a complete ring of precingular plates, analogous to what is found in Heterocapsa F. Stein, Fragilidium A.R. Loeblich, and Thecadinium Kofoid & Skogsberg in the interpretations of Balech (1988, p. 160), Sournia (1986, p. 95), and Hoppenrath et al (2005), respectively. In contrast, Wołoszyńska (1916) originally interpreted the plate as part of the sulcus, which she described as penetrating the epitheca.…”
mentioning
confidence: 98%